Kualitas Hidup Penderita Hipertensi di Wilayah Kerja UPT Puskesmas Tambang Kabupaten Kampar - Apriza Apriza (Jurnal Ners, 2025)
Hypertension or high blood pressure is a condition of increased blood pressure exceeding the normal threshold of 120/80 mmHg. Hypertension is one of the non-communicable diseases that is the leading cause of premature death worldwide. Hypertension that occurs in a person over a long period of time will cause complications in various organs of the body, namely the brain, eyes, heart, arteries, and kidneys, which will affect the quality of life of hypertension sufferers. Individuals who suffer from hypertension have a lower quality of life compared to individuals with normal blood pressure. This study aims to obtain a picture of the quality of life of hypertension sufferers in the Working Area of the UPT Tambang Health Center, Kampar Regency. This study is a type of quantitative descriptive research conducted on 301 respondents who were selected using probability sampling techniques with the simple random sampling method. The results of the study showed that most hypertension sufferers in the working area of the UPT Tambang Health Center had been diagnosed with hypertension within a period of 1-5 years, namely 156 people (51.8%). The results of the study also illustrate that most hypertension sufferers have no difficulty walking, totaling 165 people (54.8%). From the research results, it can be seen that the majority of hypertension sufferers in the working area of the UPT Tambang Health Center have good enough health based on the VAS assessment of 180 people (58.9%).